Refining output efficiency for vehicular delay tolerant network routing protocols - Rathod, Jay (2017)
Delay Tolerant Network (DTN) is a type of challenge network, which relies on intermittent nodes to communicate. Vehicular Delay Tolerant Network (VDTN) is type of DTN where the network has an unstable topology and high node mobility. These features cause congestion issues in the network leading to a greater number of message drops. To mitigate the congestion issues in VDTN, a Spray and Wait V2 routing protocol in implemented in the ONE simulator by extending the default Spray and Wait protocol. Spray and Wait V2 involved the use of Utility functionality, making the protocol more efficient comparatively. Experiment on the implemented protocols and other default protocols were conducted in two parts. Part 1 focused on creating a real world VDTN scenario and the number of nodes (cars) was varied. Part 2 focused on creating a near perfect scenario and evaluated how well the protocols performed in almost perfect scenarios. The buffer size was varied for Part 2. Results from Part 1 displayed Spray and Wait V2 has the best delivery probability, best overhead ratio and the least amount of message drops. Results from Part 2 showed that MaxProp performed the best in near perfect configurations however Spray and Wait V2 still performed superior to Spray and Wait. Hence, Spray and Wait V2 has considerable improvement in terms of message drops and delivery probability and can be implemented in VDTN. This will significantly improve the protection of the drivers as they are more probable to receive critical messages, refining their safety on the road.